Staying in touch: Taking a closer look at ER–Golgi contact sites - Sassano, Maria Livia (J Cell Biol, 2019)
ER–Golgi contact sites regulate lipid homeostasis and trafficking across the trans-Golgi network. However, their molecular nature is elusive. In this issue, Venditti et al. (2019. J. Cell Biol. https://doi.org/10.1083/jcb.201812020 and https://doi.org/10.1083/jcb.201812021) shine new light on the molecular determinants coupling lipid exchange and cargo exit with maintenance of ER–Golgi contacts.